The Effectiveness of Mathematics Learning in Limited Face-to-Face at SMP Negeri 1 Palopo - Sitti Zahirah Nurdin; Dwi Risky Arifanti; Sumardin Raupu (Proceeding International Conference on Religion, Science and Education, 2023)
This study aims to determine the effectiveness of learning mathematics in limited faceto-face at SMP Negeri 1 Palopo. This type of research is descriptive with a quantitative approach. The population is all students of SMP Negeri 1 Palopo starting from grades VII-IX for the 2021/2022 academic year, totaling 916 students. Sampling was carried out using the Proportionate Stratified Random Sampling technique. The sample was used by 90 students. Data is obtained through questionnaires that are shared directly with students. Furthermore, the research data was analyzed descriptively. The results of this study showed that the effectiveness of mathematics learning in limited face-to-face at SMP Negeri 1 Palopo is quite effective. This can be inferred from the overall number of indicators assessed, namely the quality of learning of 80.38% is considered effective, the suitability of the learning level of 79.28% is classified as effective, the incentive of 85.39% is classified as very effective and the time of 80.22% is classified as effective. Overall, the fourth percentage of indicators is 81.22% which is quite effective.